Factors Associated with Infrequent Dental Visits among Female patients attending Dental OPD of College of Dentistry, King Khalid University, Abha, KSA - Fariha Naz, Raheela Yasmin, Rehana Kausar, Saadia Bano Lone, Mehvish Sajjad, Sadia Hassan Khan, Shaherah Mekhrb, Mashael Qassim (Pakistan Journal of Medical & Health Sciences, 2022)
The aim of the present study was to find out the reasons of low frequency of dental visits by the patients having one or less than one visit per year. Materials and Methods: A questionnaire-based survey was carried out using convenient sampling technique, in the female dental OPD of College of Dentistry, King Khalid University, Abha, Saudi Arabia. Proformas were filled after interviewing patients having one or less than one per year frequency of dental visits and attending dental OPD on duty days of interviewing doctors. 159 questionnaires were filled. Frequency and percentage of each response were calculated through descriptive statistics using SPSS (V.16). Results: Lack of time was the reason given by 29% of patients, high cost of treatment by 24.5%, fear by 23.9%, difficulty in approaching dental clinics by 23.3%,unawareness by 21%, low income by 20%, personal dislike for dental treatment by 14.5%, pending the visits by 13% and lack of family support for dental treatment by 12% of patients for not attending dental clinics for regular check-ups. Conclusion: Lack of time, high cost of treatment and dental anxiety were the most common reasons for low frequency of dental visits by the patients. Unawareness about the importance of dental health was also a significant factor. Strategies should be adopted to address all the factors and to educate patients at all levels regarding importance of oral and dental health. Proper implementation of these strategies should improve the frequency of visits by the patients for regular dental-checkups. Key words: Dental visits, Frequency, Low attendance, Reasons.